Pengaruh Literasi Keuangan, Manajemen Keuangan Dan Aplikasi Keuangan Terhadap Pengembangan Usaha UMKM Kota Bandung - Dora, Yenny Maya; Rumaisa, Fitrah (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2024)
Running a business requires a true understanding of finance and financial management. This is becausethe business capital used must really be used as optimally as possible for the success of the businessbeing run. Apart from that, in the current era of advances in information technology, financialmanagement requires financial application support that can assist in business financial activities. Sothis research was carried out with the aim of finding out the influence of financial literacy, financialmanagement and financial applications on the development of MSME businesses. This research methodis descriptive quantitative. Data was obtained by distributing questionnaires to 100 MSMEs in BandungCity. The data obtained was processed and analyzed using SPSS 25. The results of the research partiallyshow that the influence of financial literacy has an influence on business development, followed byfinancial management and financial applications. And together, financial literacy, financialmanagement and financial applications have an influence on the business development of MSMEplayers. Therefore, it is necessary to increase understanding of financial literacy, financial managementand the use of financial applications for Bandung City MSMEs so that the businesses they run cancontinue to grow. This can be done through collaboration between the Bandung City Chamber ofCommerce and Industry and academics for training and mentoring